1996
DOI: 10.1002/ep.670150315
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new electrokinetic technique for decontamination of hexavalent chromium from low surface charged soils

Abstract: A new in-situ technique was developed for hexavalent chromium removal from sand. Imposition of constant potential gradient acmss the soil matrix through a graphite cathode and iron anode resulted in successful migration of chromate towards the anode. 7be hexavalent chromium ions are reduced to harmless trivalent form by chemical reaction with the anodic dissolution product, Fe2 ' .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…It is speculated that the existence of Cr(VI) in the anode reservoir is attributed to the diffusion of soluble Cr(VI) caused by the concentration gradient in the vicinity of anode and the migration of the anionic Cr(VI) ions towards the anode. Studies have shown that Cr(VI) could migrate into anode during the electrokinetic remediation [11][12][13][14][15][16][17][18][19]. The occurrence of Cr(III) in the anolyte might be attributed to:…”
Section: Redox Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…It is speculated that the existence of Cr(VI) in the anode reservoir is attributed to the diffusion of soluble Cr(VI) caused by the concentration gradient in the vicinity of anode and the migration of the anionic Cr(VI) ions towards the anode. Studies have shown that Cr(VI) could migrate into anode during the electrokinetic remediation [11][12][13][14][15][16][17][18][19]. The occurrence of Cr(III) in the anolyte might be attributed to:…”
Section: Redox Potentialmentioning
confidence: 99%
“…Most recently, Chang and Cheng [20] performed the combination of EK and ZVI for remediation of the perchlorethylene contaminated soil and the results were promising. In the past relevant EK studies [11][12][13][14][15][16][17][18][19], Cr(VI) contamination in the tested soil was low. However, the effectiveness of EK remediation of Cr(VI)-contaminated soil is strongly affected by its concentration level and reductive media in the soil.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They can predict specific benchscale laboratory experimental results with varying degrees of success. These numerical models include those developed by Yeung [74], Narasimhan and Ranjan [76], Eykholt and Daniel [107], Alshawabkeh and Acar [121,122], Eykholt [123], Hicks and Tondorf [124], Jacobs et al [125], Choi and Lui [126], Yeung and Datla [127], Denisov et al [128], Yu and Neretnieks [129,130], Haran et al [131], Liu and Lui [132], Ribeiro and Mexia [133], Jennings and Mansharamani [134], Shiba et al [135], Mattson et al [136,137], Rahner et al [138], Röhrs et al [139], Kim et al [140], Musso [141], Oyanader et al [142], Vereda-Alonso et al [143], among many others. However, none of these models can fully describe all the simultaneous processes occurring during electrokinetic remediation.…”
Section: Development In Numerical Modeling Of Electrokinetic Remediationmentioning
confidence: 99%
“…The electrokinetic process employs a low-level direct current across the contaminated medium, which induces the mobility of charged contaminants due to electromigration and electroosmotic flow (Virkutyte et al, 2004;Haran et al, 1996;Mattson and Lindgren, 1995). Electrokinetic techniques are beneficial technologies because they include low power consumption, control over the flow direction of both water and dissolved contaminants as well as confinement of contaminants in the electrode chambers that makes the subsequent treatment easier (Acar and Alshawabkeh, 1993).…”
Section: Introductionmentioning
confidence: 99%